Effects of average production and price risk on gross margin for cereal products obtained in conventionally and organic farming - Ana Ursu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The study aims to present from a technical-economic point of view aspects related to the cost behaviour, according to the cost-volume-profit analysis model and the sensitivity analysis, of cereal products (maize and wheat) grown in conventional and organic farming systems. In Romania, according to EUROSTAT statistical data, in the period 2014-202, the production harvested with wheat was increasing, on average by 823 thousand t/year, compared to organic wheat, which decreased, on average by 3.3861 thousand t/year. Maize production harvested increased, on average, by 2771.3 thousand t/year, as production yield increased by 1.184 t/ha, while organic maize production decreased by 12.413 thousand t/year. Production costs vary according to planned production levels, with differences being determined by agro-technical conditions (irrigated/non-irrigated). Estimated profit for 2022 are exteuro86/ha for non-irrigated wheat and exteuro171/ha for irrigated wheat, and exteuro91/ha (non-irrigated) and exteuro161/ha (irrigated) for organic wheat. For maize, the estimated gross profit is 94 euro/ha for non-irrigated and 225 euro/ha for irrigated, and for organic maize the gross profit to be obtained is 125 euro/ha for non-irrigated and 181 euro/ha for irrigated. However, in the context of the 2021/2022 production year the effects of all factors (political conflict in Ukraine, grain market, price volatility, inflation, production costs and growing conditions - climate conditions, soil, pedological drought, a etc.) complete the economic risk profile for the studied cereals.
Keywords: O12; P50; Q18; Q57; 330; cost-volume-profit analysis; sensitivity analysis; price volatility; wheat; maize